Listeria monocytogenes in Nature - Welshimer, H. J. (1971)
Samples from 12 farms were examined during two successive spring and early autumn seasons. L. monocytogenes was isolated from vegetation or soil taken from 11 of the 12 farms and from 6 of the 7 nonagricultural sites. A total of 27 strains were isolated from the 19 sites. The organism was not isolated from any of the autumn collections.